UKRAINIAN PAGE IN THE ANTHOLOGY OF THE ICONOGRAPHY OF THE GREAT SPHINX - Yamash, Yuri (European Science, 2024)
The article examines the anthology of the iconography of the Great Sphinx, an ancient Egyptian shrine in the Giza Valley. Special attention was paid to the paintings of the Ukrainian artist Ivan Trush, who traveled to Egypt in 1912 and had the opportunity